A critical review of model of tajdid and tajrid muhammadiyah movements - Putra Ardhana; Himad Ali (Yayasan Azhar Amanaa Yogyakarta, 2024)
As time goes by, many new sects emerge that deviate from the rules of the Islamic religion. Therefore, to give Muslims a better understanding, the meaning of tarjid and tajdid will be explained in this discussion. So that there is no misunderstanding, when his brother does something related to religion such as whudu, there is no problem for those who adhere to the Imam Shafi'i or Imam Malik madhhab; they each have their own laws. Using a qualitative approach with descriptive analysis, this research involves a comprehensive literature review on the Muhammadiyah tajdid and tajrid movement, which aims to provide an understanding of the model regarding the Muhammadiyah tajdid and tajrid movement. In the Muhammadiyah constitution, it is divided into three movement models which manifest as movement capital, namely: First: Muhammadiyah as an Islamic movement. Second: as an effort to preach amar ma'ruf nahi munkar, and third, Muhammadiyah as an effort to tajdid. Since its inception, Muhamadiyah has focused on strengthening the movement's base. Tajdid Muhammadiyah is concrete and productive, meaning that the business charities established can be felt and utilized concretely by Muslims, the Indonesian people, and everyone. The nature of Tajdid Muhammadiyah is that it is open, Tajdid Muhammad Muhammadiyah is very functionally aligned and with Muhammadiyah's ideals to make Islam a progressive religion, also a virtuous Islam that is always present as a solution to problems, including health, education and socio-economic problems. Keywords: Muhammadiyah, Tajdid Movement, Tajrid Movement